What's in a family legacy? : balancing family emotions and business growth at Luse Holdings - Ward, John L., 1945-; Luse, Ashley E. (London : Kellogg School of Management, 2017)
After decades of continuity, Luse Holdings faced a new challenge in 2015. The company needed to pivot in a changing industry context--specifically, Luse had lost a bid to a non-union competitor for the first time--and CEO and fourth-generation member Steve Luse was considering three primary options: (1) continue as is, while also adding non-union services; (2) sell part of the business to reduce family risk; or (3) sell the entire business to fund other family interests. A fourth possible option was a maximization-of-growth alternative.This decision involved more than business considerations alone. The family's legacy as an industry champion and community philanthropist also required considering all relevant stakeholders, including immediate and extended family, employees, and community. Complicating the situation was the lack of an immediately identifiable successor in the next generation of the Luse family, though several fifth-generation members had completed internships with the business--including Steve's daughter Ashley, a recent MBA graduate. Students will step into Steve's shoes as he considers what recommendations to make to the advisory board six months from now. Students can also take the perspective of Ashley, a rising next-generation member: should she join the family business?
Originally published in Ward, J. L., & Luse, A. E. (2017). What's in a family legacy? Balancing family emotions and business growth at Luse Holdings. 5-416-758. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Luse, Steve; Luse Holdings; Family-owned business enterprises -- Succession